Learners' Needs for E-Modules in Dynamic Fluid Learning Integrated with 21st Century Skills - Nabilah Ikrimah Ayani; Ratnawulan Ratnawulan; Ahmad Fauzi; Emiliannur Emiliannur; Dwi Yulia (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to describe the need for developing electronic-based teaching materials (e-modules). The research is a descriptive study conducted at a high school in Padang City, involving 140 students as participants. A questionnaire was used as the data collection instrument to assess students' needs for teaching materials and their characteristics. The questionnaire includes five indicators: 1) student characteristics, 2) implementation of physics learning, 3) use of teaching materials in physics lessons, 4) students' needs for teaching materials, and 5) students' 21st-century skills. The data collected were analyzed using descriptive statistics. The findings revealed that 1) 67% of students struggle with physics lessons, 2) 53% of students reported that feedback from teachers at the end of physics lessons is inadequate, 3) 45% of students have not used diverse teaching materials, 4) 80% of students need additional learning resources, such as teaching materials with text, images, and videos, for independent study, and 5) 51% of students have low 21st-century skills. These results underscore the need for developing electronic teaching materials (e-modules) to support physics learning